Using analytic hierarchy process (AHP) in location selection for a yarn factory: A case study - Guneri, Ali Fuat; Tiryaki, Fatma; Akkaya, Gokay (UNIV CINCINNATI INDUSTRIAL ENGINEERING, 2006)
This paper discusses the location selection problem, the applicability of Analytic Hierarchy Process (AHP) in solving such a problem, and presents a case of AHP application to the location selection for a yam factory. This method adopts a multicriteria approach that can be used for analysis and comparison of location selection. The method is based on pairwise comparison between factors that affect the location selection. Although our application was for only one specific company, there is nothing unique about the environment of the case study, and thus this approach could be generalized to any company. Significance: Location selection plays a very prominent role in long-term investments. Plant location selection is a serious problem for managers. This paper demonstrates how AHP method can be applied to the location selection problem for a yarn factory.
Keywords: location selection; analytic hierarchy process; decision making; DECISION-SUPPORT-SYSTEM; FACILITY LOCATION; CONVENIENCE STORE; FUZZY AHP; Engineering